ҚАРАҚАЛПАҚ ЭПОСЛАРЫНЫҢ ЖЫЙНАЛЫЎЫ, БАСЫП ШЫҒАРЫЛЫЎЫ ҲӘМ ИЗЕРТЛЕНИЎИНДЕ СЫРТ ЕЛ АЛЫМЛАРЫНЫҢ ТУТҚАН ОРНЫ - Алламбергенова, Г.К. (SCIENCE and SOCIETY, 2018)
The article deals with the description of the periods of the development of Karakalpak epos in foreign countries. The author of the article emphasizes the contribution of foreign scholars Sh.Valikhanov, G.Vamberi in introducing of Karakalpak eposes to other countries. The article is devoted to the issues of study of the Karakalpak epos by foreign scholars in the XX-th and at the beginming of the XXI-st century. There have been analyzed their research works, devoted to the study and propaganda of Karakalpak eposes. Special attention is given to the evaluation of the works of the German scholar Carl Reikhel done at the end of the XX-th and at the beginming of the XXI-st century and devoted to the study and publication of the Karakalpak folklore epos «Edige».